Meningkatkan Hasil Belajar Matematika Materi Perbandingan Pecahan Kelas III SDN 2 Pasigitan Kendal - Sutarti, Sutarti (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Mathematics is a general subject in Group A as a curricular program that develops attitudinal competence, knowledge competence and skill competence of students as a basis for and strengthening abilities in social, national and state life. It is said that the results of the daily mathematics assessment of students are still many who have not achieved completeness. Learning activities at SD Negeri 2 Pasigitan for grade 3 students are still classical. Teachers often use lecture and assignment methods, the teacher's learning model is less varied and does not activate students in learning activities. Teachers also have not empowered learning media that can help students understand the learning material. The research aims: (1) To find out the process of implementing the cooperative learning model with the help of image media in increasing student learning activities in Mathematics lessons on comparing fractions (2) To find out how much student learning outcomes have increased through the application of the cooperative learning model with the help of image media in lessons Mathematics material comparing fractions for Class III SDN 2 Pasigitan Semester 2 Academic Year 2021/2022. Researchers use a cooperative learning model with the help of image media. The learning process includes three cycles with planning, action, observation and reflection stages. Data collection uses tests and non-tests. Tools for collecting data include observation sheets, teacher notes, and photo documentation. Data analysis techniques include quantitative techniques and qualitative techniques. The research results show that the application of the cooperative learning model with the help of image media can increase the learning activity of comparing fractions in class III of SDN 02 Pasigitan, second semester of the 2021/2022 academic year from inactive to more active and creative. After comparing fractions through a cooperative learning model with the help of image media for class III students at SDN 02 Pasigitan semester 2 of the 2021/2022 academic year, learning outcomes increased from 58.8% to 82.35%, achieving completion above 82.75%. As elementary school teachers, you should have a high level of commitment in carrying out your duties by carrying out your main tasks professionally, reviewing and implementing various learning innovations in an effort to improve student learning outcomes with learning models and media. School Principals and School Supervisors should intensify their role as supervisors so that teachers are more orderly in administration and increase their competence through coaching.